Correlation analysis and path coefficient studies for fatty acid profile in Indian mustard (Brassica juncea L) (Journal of Oilseed Brassica, 2026)
In the present study, one hundred seventy-five genotypes of Indian mustard (Brassica juncea) were analyzed for its major fatty acid traits using correlation coefficient and path coefficient to examine the cause and consequences relationship with direct and indirect components. 175 F plants formed by crossing Pusa mehak (Indian genotype) × 2:3 Primus (East-European genotype) and selfing the F s and F s were utilized for this study. The correlation coefficient of 1 2 the major fatty acids revealed that there was positive correlation and significance for stearic acid and oleic acid (0.67), palmitic acid and linoleic acid (0.60), linolenic and oleic acid (0.50). While significant negative correlations existed between erucic acid and all other fatty acids except eicosenoic acid (0.41). It was also established that a reduction in erucic acid exhibits an elevation in both oleic and linoleic acids and a simultaneous decrease in eicosenoic acid. In path coefficient studies, when oil content as dependent character and all other residual 7 fatty acids percentage was considered as independent contributing characters, eicosenoic acid (G= 0.76 ,P=0.73) and oleic acid (G= 0.72, P=0.71) displayed high order of direct effect on oil content and it is followed by linolenic (G= 0.55, P= 0.53), erucic acid (G= 0.47, P= 0.46), linoleic acid (G= 0.35, P= 0.33). These characters also been identified as major direct and indirect contributors towards oil contents and fatty acid profile in Indian mustard. The variation in grain yield unexplained by the seven causes was considered to be due to residual effect (G= 0.28, P= 0.31), which is uncorrelated with other related factors.